Use and limitations of genome-scale metabolic models in food microbiology. (February 2022) - Somerville, Vincent; Grigaitis, Pranas; Battjes, Julius; Moro, Francesco; Teusink, Bas
Highlights: Computational models are a useful tool to understand microbial metabolism. Challenges are complex media and interactions between metabolically diverse strains. Models have addressed robustness, biotransformation and food enhancement. Future challenge is to move to community modelling. Abstract : Microbes are key to creating safe, edible and enriched fermented food products. This is largely achieved by their metabolism. Thus, the ability to understand the wiring of the complete cellular metabolism is critical to control the fermentation processes. Metabolic modelling is a useful tool for integration of large datasets to link genotype to phenotype. Here, we summarise how metabolic models are being used to address the challenges in safety, biotransformation and food enhancement in food-relevant settings. Finally, we discuss how metabolic modelling can be integrated to assess more complex scenarios such as microbial communities. Despite many remaining challenges, metabolic models hold a large potential for use in food microbiology.